Imaging gray matter with concomitant null point imaging from the phase sensitive inversion recovery sequence - Mougin, Olivier; Abdel-Fahim, Rasha; Dineen, Robert; Pitiot, Alain; Evangelou, Nikos; Gowland, Penny A. (Wiley, 2016)
Purpose